The Dolichopus planitarsis species group in the Palearctic Region with the description of a new species from the Russian Altai (Diptera: Dolichopodidae) - Barkalov, Anatolii V.; Negrobov, Oleg P.; Grichanov, Igor Ya. (Zootaxa, 2009)
The Dolichopus planitarsis species group in the Palearctic Region is defined and reviewed. It comprises eight species including one new species, Dolichopus tundrensis sp. nov., from the Altai Mountains. The species group is differentiated from other Dolichopus by the male mid tarsomere 5 which is black and flattened dorsoventrally with anterior and posterior rows of strong setae. A revised key to the species group is provided, as well as remarks on its geographical distribution.